2014
DOI: 10.3892/ijmm.2014.1648
|View full text |Cite
|
Sign up to set email alerts
|

SPARC silencing inhibits the growth of acute myeloid leukemia transformed from myelodysplastic syndrome via induction of cell cycle arrest and apoptosis

Abstract: Secreted protein acidic and rich in cysteine (SPARC) plays key roles in erythropoiesis; haploinsufficiency of SPARC is implicated in the progression of the 5q- syndrome. However, the role of SPARC in other subtypes of myelodysplastic syndrome (MDS) is not fully understood, particularly in the del(5q) type with a complex karyotype, which has a high risk to transform into acute myeloid leukemia (AML). In the present study, we investigated the role of SPARC in the proliferation and apoptosis of SKM-1 cells, an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
8
2
Order By: Relevance
“…Of note, these results differ from the recent findings in AML patients and cells where it has been shown that an increased level of SPARC expression either ectopically in vitro, or when detected in ex vivo primary leukemic blasts from AML patients, contributes to leukemia growth in vitro and aggressive disease in vivo (18). By contrast, the results from this and a previous study (22), exhibit proliferation inhibition and increased cell death after SPARC overexpression or silencing in the AML/MDS SKM-1 cell line. These contradicting results of SPARC involvement in the biology of different cell types, underscores the pleiotropic function and effects of SPARC protein in the cell life cycle and its complex role in disease where its involvement is unique sometimes promoting growth and survival, whereas it may also lead to inhibition of proliferation and apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Of note, these results differ from the recent findings in AML patients and cells where it has been shown that an increased level of SPARC expression either ectopically in vitro, or when detected in ex vivo primary leukemic blasts from AML patients, contributes to leukemia growth in vitro and aggressive disease in vivo (18). By contrast, the results from this and a previous study (22), exhibit proliferation inhibition and increased cell death after SPARC overexpression or silencing in the AML/MDS SKM-1 cell line. These contradicting results of SPARC involvement in the biology of different cell types, underscores the pleiotropic function and effects of SPARC protein in the cell life cycle and its complex role in disease where its involvement is unique sometimes promoting growth and survival, whereas it may also lead to inhibition of proliferation and apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Further association of SPARC expression to MDS treatment management has yet to be established. In a previous study (22), we developed a lentiviral vector carrying a short hairpin RNA silencer for the SPARC gene and we employed this RNA interfering technology to knock down SPARC expression in SKM-1 cells. SPARC knockdown inhibited the proliferation of SKM-1 cells by inducing cell cycle arrest at the G1/G0 phase and apoptosis through p53 elevation of caspase-9 and -3 and Fas at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were harvested, washed twice with ice-cold PBS and resuspended in binding buffer containing 1 µl of AnnexinV-PE and 5 µl of 7-AAD (KeyGen Biotech, Shanghai, China) (15). All specimens were determined by flow cytometry using CellQuest software (BD Biosciences) after incubation for 15 min at room temperature in a light-protected area.…”
Section: Assessment Of Apoptosis By Annexin V and 7-aad Stainingmentioning
confidence: 99%